Knockdown of transglutaminase-2 prevents early age-induced vascular changes in mice - Armstrong,Dinani Matoso Filho (2018)
Abstract Purpose: To determine whether the absence of transglutaminase 2 enzyme (TG2) in TG2 knockout mice (TG2-/-) protect them against early age-related functional and histological arterial changes. Methods: Pulse wave velocity (PWV) was measured using non-invasive Doppler and mean arterial pressure (MAP) was measured in awake mice using tail-cuff system. Thoracic aortas were excised for evaluation of endothelial dependent vasodilation (EDV) by wire myography, as well as histological analyses. Results: PWV and MAP were similar in TG2-/-mice to age-matched wild type (WT) control mice. Old WT mice exhibited a markedly attenuated EDV as compared to young WT animals. The TG2-/-young and old mice had enhanced EDV responses (p<0.01) as compared to WT mice. There was a significant increase in TG2 crosslinks by IHC in WT old group compared to Young, with no stain in the TG2-/-animals. Optical microscopy examination of Old WT mice aorta showed thinning and fragmentation of elastic laminae. Young WT mice, old and young TG2-/-mice presented regularly arranged and parallel elastic laminae of the tunica media. Conclusion: The genetic suppression of TG2 delays the age-induced endothelial dysfunction and histological modifications.